INTEREST LOAN IN THE PERSPECTIVE OF ISLAMIC JURISPRUDENCE (COMPARATIVE STUDIES) - Daud Rasyid (SALAM: Jurnal Sosial dan Budaya Syar-i, 2020)
AbstractTrading is a fabric of our lives, where lending and borrowing has become a contemporaneous product.  What remains constantly changing is the models and means in the transaction.  In this day and age, banks issues loans through credit cards to clients for financial transactions with fixed maturity dates and balance limits.  Cardholders will be penalized for late payment should the due amount is not settled within the given grace period.  Another example in trading activity is when a company seeks public loan funding to cover investment projects.  The capital transaction is offered in an exchange of returns in interests and derivatives awarded to participating clients for certain contract durations.  These are called interest-based banks. Since the beginning of Islam, Prophet Muhammad, Peace be upon him, prohibited this practice, which at the time was engaged by his uncle, Al-Abbas. Prophet Muhammad, Peace be upon him, firmly said: "The first usury I eliminated was the usury belonging to my uncle al-Abbâs". Islamic Sharia strictly forbids charging additional fees for loans given to borrowers. What is permissible is a business agreement is via capital cooperation and profit-sharing, following a mutual contract, and not by levying loan charges in form of additional fees.  This paper examines the problems from the perspectives of Islamic law by presenting the opinions of the schools of Fiqh and making comparisons based on the literature from each school of thought.Keywords: Loan, Interest, Ribâ, Syarîˊat, Companion of Prophet Abstrak:Dalam interaksi dagang, pinjam-meminjam tidak dapat dilepaskan dari aktifitas manusia. Sejak dulu model ini sudah ada sezaman dengan keberadaan manusia. Yang berubah hanya sarana dan model. Di zaman ini, pinjaman bank berupa kartu kredit yang memberikan pinjaman dana kepada nasabahnya untuk dipakai dalam transaksi keuangan dengan limit tertentu dan jangka waktu tertentu. Apabila waktu yang ditetapkan berakhir, maka nasabah dikenakan denda dengan kewajiban membayar uang yang dipinjamkan ditambah denda atas keterlambatan. Contoh lain, perusahaan besar membutuhkan dana besar untuk proyek bisnisnya. Ia memerlukan tambahan modal, lalu menawarkan kepada public untuk memberikan pinjaman dalam waktu yang ditentukan dengan perjanjian akan memberi imbalan berupa “bunga” atas keikut-sertaan itu. Inilah yang disebut dengan pinjaman berbunga. Sejak awal Islam, praktik ini dilarang oleh Rasul yang dulu dijalankan oleh pamannya sendiri al-Abbas. Dengan tegas Rasul mengatakan: “Riba pertama yang kuhapus ialah riba pamanku al-Abbas”. Syari’at Islam melarang keras untuk mengenakan biaya tambahan atas pinjaman yang diberikan kepada peminjam. Yang dibolehkan ialah perjanjian bisnis dengan bentuk kerjasama permodalan dan pembagian keuntungan sesuai kesepakatan, bukan pembebanan atas pinjaman dengan mengenakan tambahan biaya atas pinjaman. Makalah ini menelaah masalah tersebut dari sudut pandang Hukum Islam dengan menampilkan pendapat mazhab-mazhab Fiqh dan melakukan perbandingan berdasarkan literatur masing-masing mazhab.Kata kunci : Pinjaman, Riba, Bunga, Syariˊat, Sahabat Nabi.